Natural capital changes in Poland: Integrating spatial and economic approach - Ivan Telega; Agnieszka Telega (Economic and Environmental Studies (E&ES), 2017)
In the context of decision making, the main challenge is the assessment of changes in natural capital stocks due to conversion of ecosystems for development purposes. Ecosystems are basically a spatial concept, so the natural approach is to use GIS to evaluate land cover changes. Basic economic model of competing land uses allows us to formulate the criteria of economic rationality in the management of natural capital. The goal of this paper is a preliminary application of the criteria coming from the economic model of land uses to assess changes in land cover in Poland in the years 2000-2012.
Keywords: Q57; C61; 330; land management; ecosystem services; natural capital; Corine Land Cover; sustainability; dynamic optimization